The factors that influence job stress among school teachers in Seri Manjung Perak / Ellya Nabila Illya Kuryakin - Kuryakin, Ellya Nabila Illya (Faculty of Business and Management, 2018)
Nowadays, teachers experience job stress like they never did before. Job stress is a very important issue as it involves people’s emotion about their work and it will affect their performance. When their stress is getting worst, it will affect the effectiveness of the organization. The main purpose of this study is to explore the factors that influence job stress among school teachers in Seri Manjung, Perak. Moreover, the research aims to discover which factors, i.e. workload, student misbehaviour, interpersonal relationship and classroom resources have the most detrimental effect on job stress. The methodology is to achieve the above aim, four sets of hypothesis were proposed: the first looked into the effect of the factors, which consists of workload, student misbehaviour, interpersonal relationship and classroom resources on job stress. A questionnaire was used and participants were drawn from 110 school teachers in Seri Manjung, Perak. The finding of this study for independent variables which is workload, student misbehaviour, interpersonal relationship and classroom resources has supported the hypothesis and significantly related to the dependent variables which is job stress. For future study, it is suggested to use other variables that can increase the value of the R-Square.